KAJIANPENERAPAN SISTEM BUILDING INTEGRATED PHOTOVOLTAICS (BIPV) PADA RANCANGAN RUMAH MINIMALIS DI KOTA BANDA ACEH - Zoel Fachri; Ira Devi Sara; Rakhmad Syafutra Lubis (J-Innovation, 2016)
The potential of renewable energy in Indonesia is very large, clean and environmentally friendly. In its utilization has not been optimal pemanfataan renewable energy renewable electricity generation costs caused such solar power can't compete with the cost of energy-fueled power plant fossil remains a challenge in the energy sector. Generating statistical data in the State Llistrik 2015 the ratio of electrification in the aceh province reached 94.17% produced by fossil-fueled power plants with the largest electric energy consumption in households. Targeted national energy by 2050, an area dominated by renewable energy which is the vision of the green city Banda Aceh regarding renewable energy utilization strategy policy. The application of Building Integrated Photovoltaik (BIPV) on the minimalist house in Banda Aceh against the slope of the roof 5 °, 10 °, 15 °, 20 °, 25 °, 30 ° and 35 ° be solutions in the utilization of renewable energy. The intensity of the radiation in the city of Banda Aceh in the past year the average reach 5 kWh/m2 and the maximum temperature in the year i.e. 34.4 ° C as well as the assumption of the electric energy needs at home, minimalist type 70 of 10368 Wh/day. The results of the simulation using software Skelion get the highest PV energy estimation on minimalist House against the slope of 5 ° of 26.2 kWh/year. But in terms of the aesthetics of a house in the tropics with a good saddle roof modeling that is on a slope of 30 ° and the electric energy generated 24.5 kWh/year.